Pemanfaatan Bahan Pangan Lokal untuk Meningkatkan Pemberdayaan SDM melalui Pelatihan Pembuatan Bolu Lapis Kukus Nangka di Desa Ngrogung Kecamatan Ngebel Kabupaten Ponorogo - Puput Imroatu Sholichah; Haniatul Mukaromah (Institut Agama Islam Sunan Giri Ponorogo, 2025)
The community of Ngrogung Village, Ngebel District, has a local potential in the form of abundant jackfruit. However, its utilization is still limited to household consumption or being sold in fresh form with low economic value. This condition indicates the need for human resource (HR) empowerment through improving skills in processing local food ingredients to create added value. This community service activity aims to enhance the capacity of the community, particularly women and youth, through training in making steamed layered jackfruit cake (bolu lapis kukus nangka) as an innovative processed product. The method used was Asset Based Community Development (ABCD), which emphasizes the utilization of assets and local potential through four stages: discovery (identification of potential), dream (formulation of aspirations), design (program planning), and destiny/delivery (implementation and sustainability). The results of the activity show an increase in participants’ skills in processing jackfruit into economically valuable products, greater community awareness of the importance of utilizing local potential, and the emergence of small household-based business initiatives. The impact of this activity not only supports human resource empowerment but also opens business opportunities, strengthens family economies, and encourages community independence based on local potential.